The Development of Sipinsur Geo Site Entertainment and Recreation Attractions in Pearung Village, Humbang Hasundutan Regency - Theresia Hutahaean (Tourism, Hospitality And Culture Insights Journal, 2021)
This research aims to describe the efforts of the Department of Culture and Tourism in the development of entertainment and recreation attractions Geo Site Sipinsur In pearung village Humbahas district and to identify internal environmental and external environmental factors that occur in an effort to develop entertainment and recreation attractions Geo Site Sipinsur In pearung village Humbahas regency. The respondents in this study numbered 95 people including the community and beach tourists in pearung village, Humbahas regency. The tools used to collect data are questionnaires and likert scale techniques used to analyze and describe the results of research. The results showed that the factors in the development of entertainment and recreation attractions Geo Site Sipinsur In pearung village Humbahas district is the development of transportation, infrastructure and maintenance of facilities to improve accessibility and connectivity to and from the tourist area entertainment and recreation Geo Site Sipinsur In pearung village Humbahas District. Because it serves as promoting and servicing, transportation, infrastructure, maintenance of facilities need to be continuously improved and developed considering being able to create the value of place utility, time utility that fosters generating, and distribution in view and spot facilities for taking pictures. Where the interest of tourists entertainment and recreation Geo Site Sipinsur In pearung village Humbahas district based on the reference of visitors and beach users including transportation, adequate facilities, cleanliness and infrastructure arrangement and other supporting including housing and environment and others and also facilities for view and photo spots. As an effort of the Department of Culture and Tourism in the development of entertainment and recreation attractions Geo Site Sipinsur In pearung village Humbahas district has been done. Factors that encourage tourists nusantara users of the beach Geo Site Sipinsur In pearung village Humbahas district is the existence of good facilities and more complete.